Influence of social media on fear of sharks, perceptions of intentionality associated with shark bites, and shark management preferences - Casola, William R.; Beall, Justin M.; Peterson, M. Nils; Larson, Lincoln R.; Price, Carol S. (Frontiers in Communication, 2022)
Sharks, a critical component of marine ecosystems, represent one of the most threatened taxa globally. Shark conservation efforts are constrained by public fear and misperceptions. Positive social media-based outreach may provide one cost effective means to reduce fear of sharks and change misperceptions about shark bite intentionality. Using framing theory, which suggests that the ways in which information is presented influences how it is processed and the changes in perceptions that result from it, we experimentally evaluated impacts of positively and negatively framed YouTube videos on fear of sharks and perceptions of shark bite intentionality among participants from the coastal state of North Carolina (NC), USA in Spring 2020. Respondents took a pre-test, followed by a randomly assigned positive or negative video treatment consisting of approximately 15 minutes of shark week videos. Pre/post-test comparisons suggest positive YouTube content decreased fright by 24%, perceived danger by 27%, and perception of shark bite intentionality by 29%, whereas negatively framed media did the opposite. Negatively framed media resulted in more respondents blaming shark bites on the shark or the swimmer. Positively framed media resulted in people blaming the swimmer or no one. Positively framed media decreased support for lethal responses to shark bites, such as shark nets, hunting down sharks that bite people, and drum lines. The positive treatment increased support for responding with research, leaving the shark alone, and education. Negatively framed media decreased support for responding by leaving the shark alone or doing nothing and increased support for some lethal responses to shark bites (i.e., drum lines and hunting down sharks). When positive and negative treatments had different effect sizes, the positive treatments tended to be more impactful. Collectively these results suggest social media may be a valuable tool for leveraging the power of communication to promote shark conservation.